IMPLEMENTASI PROGRAM AYO NAIK BUS OLEH PERUM DAMRI BANDUNG - Rizqi Wahyu Pratama; Hanny Hafiar; Centurion Chendy Priyatna (Avant Garde, 2018)
This study aims to find out the process of program implementation Ayo Naik Bus by Perum DAMRI Bandung, to determine the cause of the failure of the program Ayo Naik Bus, and to know the communication patterns Perum DAMRI Bandung in overcoming the obstacles that occur in the program Ayo Naik Bus. The theory used in this research is Social Construction theory of Reality. The methodology used is qualitative approach with a case study. The research data was collected by observation, interview, online search, and literature study. The result of this research is the implementation process which originated from the idea of Ministry of Transportation which then implemented into a program by the Marketing and Development division of Perum DAMRI Bandung through special strategies with the aim to increase the interest of Bandung society to use the bus. The results of the implementation of this program are not successful because of the emergence of barriers from external and internal companies that can not be overcome. To find solutions to these problems Perum DAMRI establish a communication pattern with internal and external companies